Anthracenylporphyrins - SENGE, MATHIAS (My University, 2010)
We report the synthesis and characterization of meso-anthracenylporphyrins with zinc and nickel metal centers. A variety of novel aryl and alky meso substituted anthracenylporphyrins were synthesized via step-wise Suzuki cross-coupling reactions using anthracenyl boronates. This method was compared to standard syntheses based on condensation reactions to yield anthracenylporphyrins of the A2B2- and A3B-type. This was complemented by the synthesis of a number of the functionalized anthracene derivatives via Suzuki couplings for use in porphyrin functionalization. Selected systems were subjected to single-crystal X-ray analysis which revealed an unusual close packing for nickel(II) anthracenylporphyrins.
PUBLISHED
Keywords: porphyrins